Effect of RME-based straw and cup media on multiplication and division learning outcomes - Fatimah Azzahra; Edi Supriadi (Himpunan Pengembang Kurikulum Indonesia, 2025)
Low Mathematics learning outcomes, especially in multiplication and division, remain a persistent challenge in elementary schools. Observations at SDN Susukan 04 Pagi revealed that many third-grade students struggle with understanding abstract concepts due to limited use of concrete and contextual learning media. This study aimed to examine the effectiveness of straw and cup media based on the Realistic Mathematics Education (RME) approach in enhancing students’ Mathematics learning outcomes. A quasi-experimental method with a posttest-only control group design was used, involving 64 students selected through saturated sampling. The instrument was a 10-item essay Post-Test, tested for validity (product-moment) and reliability (Cronbach’s Alpha). Data analysis included normality (Shapiro-Wilk), homogeneity (Levene’s test), independent t-test, and effect size calculation. The results showed that the experimental group significantly outperformed the control group. The effect size analysis indicated a strong practical impact. The use of RME-based straw and cup media helped students better visualize and contextualize multiplication and division problems, promoting active learning and deeper conceptual understanding. These findings confirm that concrete media integrated with meaningful learning models can significantly improve student performance in Mathematics. Abstrak Rendahnya hasil belajar Matematika, khususnya pada materi perkalian dan pembagian, masih menjadi permasalahan yang dihadapi peserta didik sekolah dasar. Hasil observasi awal di SDN Susukan 04 Pagi menunjukkan bahwa banyak peserta didik kelas III mengalami kesulitan dalam memahami konsep abstrak karena minimnya penggunaan media konkret dan kontekstual. Penelitian ini bertujuan untuk mengetahui efektivitas media sedotan gelas berbasis Realistic Mathematics Education (RME) terhadap hasil belajar Matematika peserta didik. Metode yang digunakan adalah quasi eksperimen dengan desain posttest-only control group. Sampel terdiri dari 64 peserta didik yang dipilih melalui teknik saturated sampling. Instrumen berupa Post-Test dengan 10 soal uraian, yang telah diuji validitasnya (product moment) dan reliabilitasnya (Alpha Cronbach). Analisis data dilakukan melalui uji normalitas (Shapiro-Wilk), homogenitas (Levene’s test), uji-t, serta perhitungan effect size. Hasil penelitian menunjukkan bahwa kelompok eksperimen memperoleh hasil belajar yang secara signifikan lebih tinggi dibanding kelompok kontrol, dengan nilai effect size yang menunjukkan pengaruh besar. Media sedotan gelas berbasis RME terbukti membantu peserta didik memvisualisasikan dan mengaitkan konsep perkalian dan pembagian dengan konteks nyata, serta mendorong pembelajaran aktif dan pemahaman konseptual yang lebih mendalam. Kata kunci: efektivitas pembelajaran; hasil belajar; Matematika; media konkret; Realistic Mathematics Education (RME)